IMPLEMENTASI KEBIJAKAN PENGANGKATAN TENAGA HONORER MENJADI CALON PEGAWAI NEGERI SIPIL DI KANTOR BKD PROVINSI MALUKU UTARA - Wattimena, Meggi Fabiola; Lengkong, Daicy; Mandey, Jantje (Sam Ratulangi University, 2014)
Procurement of Civil Service is a process of activities to fill the vacancy formation. connection with this, then every Indonesian citizen who meets the requirements set out in government regulations is an equal opportunity to apply and be appointed as civil servants. But the objective conditions showed many honorary workers who have served for so long but not appointed as civil servants Civil. departed from the matter, this study intended to answer the question of how policy implementation appointment of Honorary Workers become candidates for Civil Servants. This study uses qualitative methods, this study using a sample taken at the office of the Regional Employment Agency North Maluku province by using the interview technique 7 questions to 15 respondents. Qualitative analysis consists of 3 steps first word reduction is the process pemelihan focusing on simplification and racial formations that emerge from the rough notes written on the field, the second presentation of the data that is drawing conclusions and taking action. and the third drawing conclusions / Verify that researchers draw conclusions and verify the symptoms obtained from the field. 3 steps apart from the data the researcher is also supported by documents obtained from the office of research. so from these results we can conclude that the government remain objective in the assessment of each participant is concerned and in the recruitment of civil servants Pemerintahpun take into account the ability of the regional budget because it can result in the ability to provide public services. because if the budget is siphoned off to fund the salaries, which is the public harmed. Based on these conclusions, it is suggested that there is good government or government agency does not receive honorary directly, because most of honorary workers who work now without the selection based only kedekakatan kinship and therefore the government should hold a clean selection for all contract officers in government agencies so that the results higher quality and the government should defer to lift the honorary staff of the general path of honorary workers before all the problems can be resolved in their respective areas. Keywords: Removal of Power Honoree